Exploring the effects of automated tracking of student responses to teacher feedback in draft revision: evidence from an undergraduate EFL writing course. Issue 2 (4th February 2022) - Cheng, Gary
ABSTRACT: This study aimed to investigate the impact of using an automated tracking system on the writing performance of English as Foreign Language (EFL) students in a 13-week academic writing course. Sixty-eight first year university students participated in the study. They received the same instruction on academic writing and were allocated to one of two conditions: experimental ( N = 36) or control ( N = 32). Participants in the experimental condition could use the automated tracking system to generate analysis of teacher feedback on their draft essays and of their subsequent revisions in response to the feedback received, while those in the control condition could not. The results of this study show that the system could not only support students to reflect on the quality of their revisions but also likely result in improvements in their revised texts. The findings of this study would contribute to the body of literature on effects of using technology to facilitate student reflection on multiple-draft writing.